Analisis Hukum Terhadap Perjanjian Hutang Piutang dengan Jasa Kalampa Piti di Kota/Kabupaten Bima - Wirawan, A. Rachmat; Komuna, Avelyn Pingkan; Robiansyah, Anton (Universitas Islam Negeri Alauddin Makassar, 2023)
The practice of debt receivables was used as a means to get income from giving debts with excess from the moment of return which became known as loan sharks. In Bima City, the practice of loan sharking became known as the